1987
DOI: 10.1084/jem.165.4.1041
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of the major iron-regulated protein expressed by pathogenic Neisseriae.

Abstract: This report describes a method to purify the major iron-regulated protein (MIRP) expressed by N. gonorrhoeae and N. meningitidis. This purification procedure involves maximal expression of the MIRP by growing the organisms on iron-limited media; cellular disruption by sonication followed by centrifugal fractionation; selective solubilization of the MIRP with the cationic detergent hexadecyltrimethylammonium bromide; cation-exchange chromatography in the presence of this detergent; and gel filtration chromatogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
46
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 36 publications
8
46
0
Order By: Relevance
“…S1 under "Supporting Information"). These profiles are similar to the FBP purified from gonococci by Mietzner et al (18). Crystallization trials were successful and confirmed the high purity of the protein.…”
Section: Overexpression and Characterization Of Nfbpsupporting
confidence: 65%
See 1 more Smart Citation
“…S1 under "Supporting Information"). These profiles are similar to the FBP purified from gonococci by Mietzner et al (18). Crystallization trials were successful and confirmed the high purity of the protein.…”
Section: Overexpression and Characterization Of Nfbpsupporting
confidence: 65%
“…The synergistic anion binding properties of transferrins including their role in metal binding and release have been well documented (14 -16), but only recently have the synergistic anion binding properties of bacterial FBP been investigated (9,17). The FBP from N. gonorrhoeae (nFBP) has been biochemically characterized (18) and subsequently expressed in Escherichia coli (19,20). It has been reported that a large excess of NaHCO 3 increases the iron binding capacity of apo-FBP (21).…”
mentioning
confidence: 99%
“…They both have the ability to reversibly bind ferric iron, and they share similar binding affinities (40). Also, only a single ferric ion binds per lobe (two for transferrin and one for FbpA), and the ferric iron-binding sites are similar (97,103). The crystal structure revealed that identical amino acid residues in transferrin and FbpA, i.e., two tyrosines, a histidine, and a glutamic acid, coordinate the iron atom but that these amino acids arise from different regions of FbpA than of transferrin (42).…”
Section: Transferrin and Lactoferrin Receptorsmentioning
confidence: 99%
“…FbpA is one of the major iron-regulated proteins and has been identified in all pathogenic Neisseria species (20,99,101). It has an apparent molecular mass of 37 kDa and is very basic (pI of Ͼ9.35) (97,98). The role of Fbp in the periplasmic transport of iron was first indicated by its localization to the periplasm and its transient association with 55 Fe acquired from 55 Fe-labeled human transferrin (19,40).…”
Section: Transferrin and Lactoferrin Receptorsmentioning
confidence: 99%
“…The gonococcal 37,000-dalton protein was purified by a combination of selective extraction with cetyltrimethylammonium bromide and column chromatography and used to produce both rabbit monospecific antiserum and murine monoclonal antibodies (39). Using these reagents, Mietzner et al (38) found that this protein was antigenically conserved among strains of N. gonorrhoeae, N. meningitidis, N. lactamica, and N. cinerea.…”
Section: Iron Metabolismmentioning
confidence: 99%